1996
DOI: 10.1097/00004647-199611000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Fragment of Amyloid Precursor Protein Accumulates in Hippocampus after Global Forebrain Ischemia

Abstract: Summary:We developed an antibody specific to f3-amy loid precursor protein (f3APP) fragments possessing the exact amino terminus of the f3-amyloid peptide and ex amined its induction in postischemic hippocampus, In control hippocampus, this APP fragment was lightly ob served in pyramidal neurons of CA sectors and dentate granule cells, Transient forebrain ischemia enhanced ac cumulation of the APP fragment in CAl pyramidal neu rons, Seven days after the ischemia, while the APP frag ment was still observed in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…Ischemia, hypoglycemia, and traumatic brain injury, a condition that has been shown to put neurons under metabolic stress (Xiong et al, 1997), all up-regulate A␤PP and its mRNA in animal models and culture systems (Hall et al, 1995;Jendroska et al, 1995;Yokota et al, 1996;Shi et al, 1997;Murakami et al, 1998). Not only does energy deficiency and Ca(II) dysregulation promote A␤PP expression, they also route the metabolism of A␤PP from the nonamyloidogenic to the amyloidogenic pathway.…”
Section: Amyloid-␤ and Alzheimer Disease: The Alternate Hypothesismentioning
confidence: 99%
“…Ischemia, hypoglycemia, and traumatic brain injury, a condition that has been shown to put neurons under metabolic stress (Xiong et al, 1997), all up-regulate A␤PP and its mRNA in animal models and culture systems (Hall et al, 1995;Jendroska et al, 1995;Yokota et al, 1996;Shi et al, 1997;Murakami et al, 1998). Not only does energy deficiency and Ca(II) dysregulation promote A␤PP expression, they also route the metabolism of A␤PP from the nonamyloidogenic to the amyloidogenic pathway.…”
Section: Amyloid-␤ and Alzheimer Disease: The Alternate Hypothesismentioning
confidence: 99%
“…Most important, we have demonstrated that reduced O 2 levels alone can induce formation of A␤P-mediated Ca 2ϩ influx. As described in the Introduction, A␤Ps are the cleavage products derived from amyloid precursor protein (5,6), and levels of this precursor have been shown to increase following ischemia (9,10). The enhanced Ca 2ϩ influx reported here may therefore be an important contributory factor to the increased incidence of dementias and amyloid deposition following cerebral ischemia, leading to neurotoxicity through excessive transmitter release.…”
Section: Discussionmentioning
confidence: 58%
“…Since APP is generally perceived to be neuroprotective, this increased expression of APP can be considered a defense mechanism against ischemia. However, increased APP levels seen in ischemia would also permit increased formation of A␤Ps, which cause neuronal damage and death (4); and indeed, A␤P production is increased following both mild and severe ischemia (9,10). Thus, a clear link exists between ischemic insult and elevation of damaging A␤P levels.…”
mentioning
confidence: 99%
“…Animals after focal and global ischemic brain injury with a survival time up to 1 year presented increased brain immunoreactivity to the -amyloid peptide and as well as to the N-and C-terminal of amyloid precursor protein. The staining was observed extracellularly and intracellularly (Pluta et al, 1994b;Hall et al, 1995;Tomimoto et al, 1995;Horsburgh, Nicoll, 1996a;Ishimaru et al, 1996a;Yokota et al, 1996;Pluta et al, 1997b;Pluta et al, 1998b;Lin et al, 1999;Pluta 2000;Lin et al, 2001;Sinigaglia-Coimbra et al, 2002;Fujioka et al, 2003;. Different fragments of amyloid precursor protein were noted in astrocytes, neurons, oligodendrocytes, and microglia (Banati et al, 1995;Palacios et al, 1995;Pluta et al, 1997b;Nihashi et al, 2001;Pluta, 2002a;Pluta2002b;Badan et al, 2003;Badan et al, 2004).…”
Section: Amyloid Precursor Protein and β-Amyloid Peptide After Ischemiamentioning
confidence: 97%
“…Multifocal and widespread different kinds of amyloid plaques were observed mainly in the ischemic hippocampus, brain and entorhinal cortex, and corpus callosum, and subventriculary (Pluta et al, 1994b;Pluta et al, 1997b;Pluta et al, 1998b;Pluta 2000;Pluta 2003;Pluta 2005;Pluta et al, 2009;Pluta et al, 2010). The accumulation of the -amyloid peptide in astrocytes and the C-terminal of amyloid precursor protein in ischemic neurons underline the likely importance of these two proteins in ischemic brain injury cascade of degeneration (Pluta et al, 1994b;Yokota et al, 1996;Pluta 2002b;Badan et al, 2003;Badan et al, 2004). Moreover, the above parts of precursor deposits suggest that these fragments of precursor may initiate synaptic pathology and finally promote retrograde neuronal death after ischemic injury (Oster-Granite et al, 1996).…”
Section: Amyloid Precursor Protein and β-Amyloid Peptide After Ischemiamentioning
confidence: 99%